2015
DOI: 10.1021/acs.jmedchem.5b01441
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Nanomolar Dengue and West Nile Virus Protease Inhibitors Containing a 4-Benzyloxyphenylglycine Residue

Abstract: The dengue virus (DENV) and West Nile Virus (WNV) NS2B-NS3 proteases are attractive targets for the development of dual-acting therapeutics against these arboviral pathogens. We present the synthesis and extensive biological evaluation of inhibitors that contain benzyl ethers of 4-hydroxyphenylglycine as non-natural peptidic building blocks synthesized via a copper-complex intermediate. A three-step optimization strategy, beginning with fragment growth of the C-terminal 4-hydroxyphenylglycine to the benzyloxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
133
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(140 citation statements)
references
References 59 publications
(144 reference statements)
5
133
2
Order By: Relevance
“…The flaviviral proteases have a strong preference for substrates with dibasic or polybasic recognition sequences [49][50][51] . Consequently, the recognition motifs in inhibitors also tend to incorporate basic or polar functionalities, which may partially explain the lower efficacy often observed in cell-based assays relative to biochemical assays, as the compounds have low passive membrane permeability [52][53][54][55][56] . The substrate-binding residues and the substrate recognition patterns of the protease are well conserved across the flaviviruses and therefore hold promise for the development of inhibitors with broad activity.…”
Section: Ns3 Protease Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The flaviviral proteases have a strong preference for substrates with dibasic or polybasic recognition sequences [49][50][51] . Consequently, the recognition motifs in inhibitors also tend to incorporate basic or polar functionalities, which may partially explain the lower efficacy often observed in cell-based assays relative to biochemical assays, as the compounds have low passive membrane permeability [52][53][54][55][56] . The substrate-binding residues and the substrate recognition patterns of the protease are well conserved across the flaviviruses and therefore hold promise for the development of inhibitors with broad activity.…”
Section: Ns3 Protease Inhibitorsmentioning
confidence: 99%
“…Numerous studies have focused on the development of protease inhibitors derived from a substrate-mimicking peptide. Strategies included incorporation of a carboxyterminal electrophile 52,54,[73][74][75] , optimization of the N-terminal capping moiety 53,56,76,77 , and modulation of the P 1 and P 2 basic residues through non-natural building blocks 53,78 . Aldehydic inhibitors displayed low micromolar to nanomolar affinity for DENV serotype 2 (DENV-2) 74 and WNV 52,75 proteases.…”
Section: Ns3 Protease Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, DENV/WNV protease inhibitors targeting P site pockets with nanomolar activity in enzymatic assays have been reported (K i ϭ 12 nM and 39 nM) (15). Since these inhibitors are highly polar, possibly underlying the micromolar-level activity in cell-based assays, incorporating the critical hydrophobic interactions we identified at P3= or P4= pockets (17) is a strategy to reduce the hydrophilicity.…”
Section: Discussionmentioning
confidence: 99%
“…While most of these inhibitors bind with only micromolar affinity, a recent study found inhibitors with nanomolar K i values (15). However, the potential challenge in targeting dengue virus protease is that this enzyme has a P side substrate sequence preference similar to those of several human serine proteases (furin RXRR, thrombin P1 R, and trypsin P1 R); hence, P side-based inhibitors are not designed to be specific to the viral protease.…”
mentioning
confidence: 99%